Soundings in Cultural Criticism : Perspectives and Methods in Culture, Power, and Identity in the New Testament - Lozada, Francisco, 1965- (Book collections on Project MUSE., 2013)
"A number of disciplines aligned under "cultural criticism" have changed the shape of contemporary biblical studies not only by offering new methods but by questioning old goals and proposing new ones. Soundings in Cultural Criticism offers a collection of succinct essays in these fields by some of the foremost scholars in New Testament studies. Questions of historical reconstruction, textual interpretation, and present cultural deployment are addressed in an ideal second textbook for New Testament courses."--